Active learning with research based on three principles of higher education - Istiningsih, Istiningsih; Unruh, Thomas; Sutrisno, Sutrisno; Kurniawati, Urip Meilina (Journal of Education and Learning (EduLearn), 2024)
This study aims to determine how using an active learning model based on the three higher education principles can improve students' active learning. Qualitative research methods were applied in this study, with data collection through interviews, literature study, and observation. The results showed that active learning based on the three higher education principles was included in the "good" or "acceptable" category. The application of this model can make this campus a place with a positive academic atmosphere that enhances and supports collaboration, discussion, and positive and critical thinking. The novelty of this research lies in the use of active learning with mini-research projects, which are developed based on university principles and embody it. The hope is that this can help solve problems in the student learning process at the State Islamic University Sunan Kalijaga, Yogyakarta, Indonesia. The expected implication is that the university's policy supports applying the model to resolve learning problems and build real scientists for students.